Pelaksanaan dan penguatkuasaan halal di Malaysia - Badarulzaman, Muhammad Hafiz; Abdul Wahab, Harlida; Azhar, Alias; Ahmad Sharif, Nurretina (Universiti Teknologi Malaysia, 2016)
The enforcement agency is one of the bodies that responsible for the issue of halal. Each agency is authorized by the respective statute and enactment in enforcing the regulation and law on halal goods and products.Although the implementation and enforcement of halal in Malaysia is seen as comprehensive, the issues on weakness and lameness of the agencies are still being debated especially matters related to procedures and conflict of jurisdictions.This paper focuses on the jurisdiction of the enforcement agencies pertaining to halal matters.The paper also will discuss and elaborate the legal issues and hiccups due to halal.Firstly, the jurisdiction of enforcement agencies will be discussed throughout this paper.Then this paper will analyze the procedures and statutory provisions as to see whether all the processes and current legislation s are protecting the consumers on halal food consumption.Notwithstanding of statutory provisions, the finding of this paper is based on interviews with the enforcement agencies of halal products.A few recommendations have been suggested as to improve the lacuna pursuant to the roles and jurisdictions of the enforcement agencies.